2016
DOI: 10.1098/rspb.2015.2691
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic recombination counteracts male-biased mutation (male-driven evolution)

Abstract: Meiotic recombination is believed to produce greater genetic variation despite the fact that deoxyribonucleic acid (DNA)-replication errors are a major source of mutations. In some vertebrates, mutation rates are higher in males than in females, which developed the theory of male-driven evolution (male-biased mutation). However, there is little molecular evidence regarding the relationships between meiotic recombination and male-biased mutation. Here we tested the theory using the frog Rana rugosa, which has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…() reported a distribution of R. rugosa , based on the morphology of the sex chromosomes in frogs collected from 24 sites in Japan. Recently, Miura and co‐workers reported two different distribution maps of R. rugosa frogs but without showing any sampling sites of the frogs (Mawaribuchi et al., ; Miura, Ohtani, Ogata, & Ezaz, ). To clarify the origin of the sex chromosomes in the different groups, it is necessary to have a refined map of the distribution in Japan of R. rugosa with genetically different backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…() reported a distribution of R. rugosa , based on the morphology of the sex chromosomes in frogs collected from 24 sites in Japan. Recently, Miura and co‐workers reported two different distribution maps of R. rugosa frogs but without showing any sampling sites of the frogs (Mawaribuchi et al., ; Miura, Ohtani, Ogata, & Ezaz, ). To clarify the origin of the sex chromosomes in the different groups, it is necessary to have a refined map of the distribution in Japan of R. rugosa with genetically different backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that dmy and dm-W have evolved under recombination suppression. We previously reported that recombination suppression might lead to accumulation of DNA replication errors during population and species diversification (Mawaribuchi et al., 2016). Therefore, it is possible that amino acid substitutions might occur with increased frequency under the suppression of recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the East group of G. rugosa has no unique adult morphology sharply distinguishing all the other groups, it had significantly less 0761-0770, 1168, 2025, 2032, 2033, 2037, 2038, 2047, 2141, 2142, 2324, 2326-2331, 2333-2336 Etymology. The specific epithet is from a Latin noun denoting relic, alluding to the facts that the species represents a basic stock of Japanese Glandirana existing far before the western G. rugosa was derived and leaves a part of its own genome within the heteromorphic sex chromosomes of G. rugosa (Miura et al 1998;Miura 2007;Mawaribuchi et al 2016).…”
Section: Degree Of Development Of Ventral Glands In Larvaementioning
confidence: 99%